Contemporary Economic Perspectives in Education - De Witte, Kristof (Book collections on Project MUSE., 2015)
Economists are well placed to study education. They are intrinsically interested in (public) spending. They want to examine whether resources are spent in an effective (i.e., doing the right things) and efficient (i.e., doing things right) way. By focusing on educational efficiency, economists can provide intuitive insights that engender more value for money. Moreover, the effectiveness concerns are related to the "evidence-based education" idea. Contemporary Economic Perspectives in Education contributes to this growing field of "education economics." This book provides a detailed approach to how economists treat earlier evidence, how they avoid measurement problems, and how they measure efficiency. Applications covered include the underperformance of boys, efficiency and equity in education, and inter-industry wage differentials in the health sector.